Isothermal and nonisothermal crystallization kinetics of bio-sourced nylon 69 - Sun, Zhijuan; Wang, Xiao; Guo, Fei; Jiang, Chunyue; Pan, Qinmin (Chinese journal of chemical engineering, 2016)
Bio-sourced nylon 69, one of promising engineering plastics, has a great potential in developing sustainable tech- nology and various commercial applications. Isothermal and nonisothermal crystallization kinetics of nylon 69 is a base to optimize the process conditions and establish the structure-property correlations for nylon 69, and it is also highly beneficial for successful applications of nylon products in industry. Isothermal and nonisothermal crystallization kinetics has been investigated by differential scanning calorimetry for nylon 69, bio-sourced even-odd nylon. The isothermal crystallization kinetics has been analyzed by the Avrami equation, the calculated Avrami exponent at various crystallization temperatures falls into the range of 2.28 and 2.86. In addition, the Avrami equation modified by Jeziorny and the equation suggested by Mo have been adopted to study the nonisothermal crystallization. The activation energies for isothermal and nonisothermal crystallization have also been determined. The study demonstrates that the crystallization model of nylon 69 might be a two- dimensional （circular） growth at both isothermal and nonisothermal crystallization conditions. Furthermore, the value of the crystallization rate parameter （K） decreases significantly but the crystallization half-time （t1/2） increases with the increase of the isothermal crystallization temperature. To nonisothermal crystallization, the crystallization rate increases as the cooling rate increases according to the analysis of Jeziorny＇s theory. The re- sults of Mo＇s theory suggest that a faster cooling rate is required to reach a higher relative degree of crystallinity in a unit of time, and crystallization rate decreases when the relative degree of crystallinity increases at nonisothermal crystallization conditions.